Physico-Chemical Analysis of Effluents from Dairy Industry - V. P. Pawar, A.S. Kolhe and (Recent Research in Science and Technology, 2011)
The treated and untreated effluents samples from dairy industry were collected and brought in to laboratory for studying physicochemical parameters like pH, temp, color, DO, BOD, COD, TDS, TSS, TS, Chloride Sulphate, Oil & grease were analyzed.